2017
DOI: 10.1007/s10695-017-0383-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood glucose level on acute stress response of grass carp Ctenopharyngodon idella

Abstract: Stress has a considerable impact on welfare and productivity of fish, and blood glucose level of fish may be a factor modulating stress response. This study evaluated the effect of blood glucose level and handling on acute stress response of grass carp Ctenopharyngodon idella. Fish were intraperitoneally injected with glucose at 0, 0.2, 0.5, and 1.0 mg g body mass (BM) and then were exposed to handling for 5 min. Glucose injection resulted in increase of plasma glucose level and liver glycogen content and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 34 publications
4
17
0
Order By: Relevance
“…Blood glucose plays an essential role as an indicator of fish physiology, especially the stress response on grass carp fish [17]. Similar research has also been reported that the glucose level in fish is related to the stress response caused by some factors such as high stocking density [18], environmental disturbance [19], salinity [20], and pollutant of heavy metal [20].…”
Section: Introductionmentioning
confidence: 54%
“…Blood glucose plays an essential role as an indicator of fish physiology, especially the stress response on grass carp fish [17]. Similar research has also been reported that the glucose level in fish is related to the stress response caused by some factors such as high stocking density [18], environmental disturbance [19], salinity [20], and pollutant of heavy metal [20].…”
Section: Introductionmentioning
confidence: 54%
“…Glucose is majorly involved in necessity-based transformation of chemical to mechanical energy. Being a primary energy molecule, it is extremely sensitive to varying levels of stress and its regulation is done according to the feedback mechanism (Jiang, Wu, Huang, Ren, & Wang, 2017). Wells and Pankhurst (1999) have also reported a positive correlation of stress with glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The blood glucose level of fish may be a factor modulating stress response and highly dependent on feeding status. Jiang et al, (2017) stated that the increased glucose concentrations may cause hyperglycemia due to the reaction of the hormone affected by stress. Such a raise may be due to the increased reaction of stressed fish to gluconeogenesis to meet their additional energy requirement.…”
Section: Discussionmentioning
confidence: 99%